Isotopic effects in partially deuterated piezoelectric crystals of Rochelle salt - Levitskii, R.R.; Zachek, I.R.; Moina, A.P.; Andrusyk, A.Ya. (Condensed Matter Physics, 2004)
We develop a theory for dielectric, piezoelectric, and elastic properties of partially deuterated (quenched disorder) crystals of Rochelle salt with taking into account the piezoelectric coupling. Results of numerical calculations are presented for a completely deuterated Rochelle salt and compared with available experimental data. Isotopic effect is explored within the mean crystal approximation, as well as within the developed theory using different trial sets of the fitting parameters. Theory predictions are given for the temperature and composition dependences of the calculated characteristics for partially deuterated crystals. Запропоновано теорію діелектричних, п’єзоелектричних і пружних властивостей частково дейтерованих (нерівноважний безлад з повним сортовим хаосом) кристалів сегнетової солі з врахуванням п’єзоелектричних взаємодій. Представлені результати числових розрахунків для повністю дейтерованої сегнетової солі порівнюються з наявними експериментальними даними. Ізотопічний ефект чисельно досліджується в наближенні середнього кристалу та в рамках запропонованої теорії при різних пробних значеннях параметрів моделі. Наведені передбачені теорією для частково дейтерованих систем залежності розрахованих характеристик від температури та рівня дейтерування.